2014
DOI: 10.1186/1478-4505-12-13
|View full text |Cite
|
Sign up to set email alerts
|

National research for health systems in Latin America and the Caribbean: moving towards the right direction?

Abstract: BackgroundNational Research for Health Systems (NRfHS) in Latin America and the Caribbean (LAC) have shown growth and consolidation in the last few years. A structured, organized system will facilitate the development and implementation of strategies for research for health to grow and contribute towards people’s health and equity.MethodsWe conducted a survey with the health managers from LAC countries that form part of the Ibero-American Ministerial Network for Health Education and Research.ResultsFrom 13 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 6 publications
(5 reference statements)
0
35
0
5
Order By: Relevance
“…The role of advice, particularly in the form of technical guidance, was pronounced in studies concerning vaccines [48,49], health technology assessment [50][51][52] and pharmaceutical policy [53]. WHO seems to be well-positioned in this process as some studies focused on its ability to establish technical guidelines and convene diverse groups of stakeholders [53][54][55][56]. On the other hand, input from civil society organisations was seen as a crucial element of forming deliberative policy dialogue [57][58][59][60].…”
Section: Types Of Knowledgementioning
confidence: 99%
“…The role of advice, particularly in the form of technical guidance, was pronounced in studies concerning vaccines [48,49], health technology assessment [50][51][52] and pharmaceutical policy [53]. WHO seems to be well-positioned in this process as some studies focused on its ability to establish technical guidelines and convene diverse groups of stakeholders [53][54][55][56]. On the other hand, input from civil society organisations was seen as a crucial element of forming deliberative policy dialogue [57][58][59][60].…”
Section: Types Of Knowledgementioning
confidence: 99%
“…Not only were these two countries the most productive in the region, by far, but the three journals publishing the largest number of articles on the topic were from the same two countries. This finding is not surprising, as Brazil accounts for over half the investment in research and development in the Latin American region, followed by Mexico and Argentina (Becerra-Posada, Menayo, Guantal, & de Haan, 2014; RICYT, 2013). These three countries represent 90% of the investment in the entire region, and our findings of uneven productivity of articles on this topic among SsLA countries seem to be in direct relation to their investment in research and development.…”
Section: Discussionmentioning
confidence: 99%
“…Institutions hosted in high-income countries in the Region reported 5 and 10 (303) *************************** Medline search strategy globally 1 (map or mapping or production or productivity or ((bibliometric or situation) adj2 analysis) or (baseline adj2 assessment)).ti,ab. issuing calls for proposals annually (37.8%), while institutions hosted within high-to-middle-and low-tomiddle-income countries did not report issuing such calls (28.8% and 28.4%, respectively).…”
Section: Training and Capacity Buildingmentioning
confidence: 99%
“…Mapping studies have been attempted in Africa (2), Canada (3), Europe (4), Latin America and the Caribbean (5). Recent studies in the World Health Organization (WHO) Eastern Mediterranean Region have revealed that the performance of health systems research is weak across all sectors, including governance, finance, workforce, medical and other technology, health information and service delivery.…”
Section: Introductionmentioning
confidence: 99%